National Politics Study, 2004 - Jackson, James S. (James Sidney) ([Verlag nicht ermittelbar], 2009)
The primary goal of the National Politics Study (NPS) was to gather comparative data about individuals' political attitudes, beliefs, aspirations, and behaviors at the beginning of the 21st century. Exploring the nature of political involvement and participation among individuals from different racial and ethnic groups, the survey included questions about voting preferences, party affiliation, organizational membership, immigration, racial consciousness, acculturation, and views of government policies.